Овоот улаан хүдрийн талбайн геологийн тогтоц, структур, хэтийн төлөв - Д.Отгонбаатар; Б.Тамир; Б.Өсөх-Эрдэнэ; С.Ганбаатар (Geological Issues, 2025)
In the Ovoot Ulaan ore field, exploration and verification works — including geological prospecting and control, geophysical surveys, drilling, and sampling— were conducted on previously identified occurrences such as the epithermal gold showings Khuren Tsav and Mukhar Khar (site 8825f), and the porphyry copper showing Khalzan Uul (site 8830f). Resource assessments were carried out at both the occurrence and ore-field scales. For each showing, supporting documentation and geological-mineral maps were updated at scales of 1:10000 to 1:25000 and hypotheses on the genetic types of the occurrences were proposed. Additionally, comprehensive maps of the ore field — including geological, mineralization, structural, and resource distribution maps — were prepared at scales ranging from 1:50000 to 1:100000.